2011
DOI: 10.1093/jxb/err039
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatidylcholine-hydrolysing phospholipase C NPC4 plays a role in response of Arabidopsis roots to salt stress

Abstract: Phosphatidylcholine-hydrolysing phospholipase C, also known as non-specific phospholipase C (NPC), is a new member of the plant phospholipase family that reacts to environmental stresses such as phosphate deficiency and aluminium toxicity, and has a role in root development and brassinolide signalling. Expression of NPC4, one of the six NPC genes in Arabidopsis, was highly induced by NaCl. Maximum expression was observed from 3 h to 6 h after the salt treatment and was dependent on salt concentration. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 65 publications
(80 reference statements)
1
64
1
Order By: Relevance
“…Based on these results, 10 mM AlCl 3 was chosen as a working concentration for in situ measurements of NPC activity in following experiments. In contrast to NPC activity in situ in Arabidopsis seedlings under salt stress, 25 here we observed negative effect of Al on DAG production. Thus, the possible influence of Al ions on BODIPY-PC incorporation into the roots of Arabidopsis seedlings exposed to Al treatment was examined by laser scanning confocal microscopy.…”
Section: Please Scroll Down For Articlecontrasting
confidence: 99%
See 2 more Smart Citations
“…Based on these results, 10 mM AlCl 3 was chosen as a working concentration for in situ measurements of NPC activity in following experiments. In contrast to NPC activity in situ in Arabidopsis seedlings under salt stress, 25 here we observed negative effect of Al on DAG production. Thus, the possible influence of Al ions on BODIPY-PC incorporation into the roots of Arabidopsis seedlings exposed to Al treatment was examined by laser scanning confocal microscopy.…”
Section: Please Scroll Down For Articlecontrasting
confidence: 99%
“…Changes of phospholipase A 2 activity in vitro, 12 phospholipase D (PLD) activity 13,14 and phosphatidylinositol-specific phospholipase C (PI-PLC) activity [15][16][17] after Al treatment were demonstrated. In addition to PI-PLC, non-specific phospholipase C (NPC, PC-PLC in prokaryotes and animals), an enzyme that is able to hydrolyse phosphatidylcholine (PC) instead of phosphatidylinositol 4,5-bisphosphate (PIP 2 ), was characterized in plants 18 in relation with a number of different cell processes or stress condition [18][19][20][21][22][23][24][25][26] including Al stress. 27,28 Studies of the target of Al action in plants have demonstrated that Al binds to the apoplast 29 and changes the properties of the PM.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Diacylglycerol produced by NPC4 can be converted to phosphatidic acid, which acts as a signaling molecule and is also involved in ABA signaling (Jacob et al, 1999;Testerink and Munnik, 2005;Peters et al, 2010). Analyses of npc4 mutants revealed its role in salt, osmotic stress, and ABA responses (Peters et al, 2010;Kocourková et al, 2011). UGE activity has been implicated to provide UDP-Gal for cell wall and galactolipid biosynthesis (Dörmann and Benning 1998;Rösti et al, 2007).…”
Section: Identification Of Oipsmentioning
confidence: 99%
“…In A. thaliana plants subjected to salinity stress, the activity of NPC was increased, promoting the production of DAG by 4-fold. 20 Phosphate starvation of A. thaliana upregulates AtNPC4 and AtNPC5, which is for the accumulation of DAG and the supply of inorganic phosphate; 21,22 Later during phosphate starvation, the PC content is transiently increased, before its rapid decrease which coincides with an increase in DAG content, indicating most of the newly synthesized DAG is derived via the PC/PLC pathway. 23 In tobacco cell cultures, treatment with brassinolide raises the DAG content within 15 min through the elevation of PC/PLC activity in a concentration-dependent manner; at the same time the size of the PA pool is not significantly increased.…”
Section: Increasing Evidence For Dag Acting As a Signaling Molecule Imentioning
confidence: 99%